I hope this information helps some people who have trouble figuring out the AES key scrambler.
k = normal key
x = keyX
y = keyY
C = constant
let's algebra !!!!
let's start with
Solve for k
Solve for x
How to solve the AES key scrambler
k = normal key
x = keyX
y = keyY
C = constant
let's algebra !!!!
let's start with
Code:
k = (((x <<< 2) ^ y) + C) <<< 87
Code:
k = (((x <<< 2) ^ y) + C) <<< 87
Code:
k = (((x <<< 2) ^ y) + C) <<< 87 >>> 87 >>> 87 (k >>> 87) = ((x <<< 2) ^ y) + C - C - C ((k >>> 87) - C) = (x <<< 2) ^ y...